Establishing the Communications Network of the Caribbean Tsunami Early Warning system (CCS [Georgetown]GY, 2005)
Describes a project that seeks to develop a platform for real time acquisition and dissemination of seismic data; develop information sharing protocols; and, educate coastal communities on tsunami hazard appropriate actions to be taken.
Keywords: TELECOMMUNICATIONS NETWORKS